Réévaluer le rôle de la société civile dans la transition démocratique paraguayenne (1989-2019) - Julien Demelenne; Damien Larrouqué (Caravelle)
The academic literature presents Paraguayan civil society as fragile or atomized. We wish to put in perspective this pessimistic and even conservative vision, by demonstrating that civil society has been an important player in the democratic transition. The insurrectionary episode of the 1999 Marzo Paraguayo constitutes a major tipping point in the evolution of relations between civil society, political class and military power.